1979
DOI: 10.1007/bf01953225
|View full text |Cite
|
Sign up to set email alerts
|

Isometric relaxation in rat myocardium: Load dependence and influence of caffeine

Abstract: When caffeine plus calcium is added to the perfusing medium, isometric relaxation of rat myocardium is no longer affected by length changes occurring during the twitch. The dependence of isometric relaxation on the initial muscle length is still present and more pronounced after caffeine addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Moreover, relaxation has recently been shown to be sensitive to the level of external load in both mammalian heart muscle (Brutsaert et al, 1978b(Brutsaert et al, , 1980 and in spontaneously beating single cardiac cells (Lecarpentier et al, 1979) in which the sarcoplasmic reticulum was still functional. Intracellular calcium-sequestering systems, particularly the sarcoplasmic reticulum, have been assumed to account partially for this property, which disappears in mammalian heart muscle treated with caffeine (Lecarpentier et al, 1979;Poggesi et al, 1979), and which is not observed in frog myocardium (Brutsaert et al, 1978b). The present study extends these observations by examining sarcomere kinetics during cardiac relaxation, in both "isotonic* and 'isometric* contractions, and demonstrates that two mechanisms are involved during cardiac relaxation.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Moreover, relaxation has recently been shown to be sensitive to the level of external load in both mammalian heart muscle (Brutsaert et al, 1978b(Brutsaert et al, , 1980 and in spontaneously beating single cardiac cells (Lecarpentier et al, 1979) in which the sarcoplasmic reticulum was still functional. Intracellular calcium-sequestering systems, particularly the sarcoplasmic reticulum, have been assumed to account partially for this property, which disappears in mammalian heart muscle treated with caffeine (Lecarpentier et al, 1979;Poggesi et al, 1979), and which is not observed in frog myocardium (Brutsaert et al, 1978b). The present study extends these observations by examining sarcomere kinetics during cardiac relaxation, in both "isotonic* and 'isometric* contractions, and demonstrates that two mechanisms are involved during cardiac relaxation.…”
supporting
confidence: 54%
“…3, March 1985al., 1978a, which destroys both sarcolemma and sarcoplasmic reticulum (Orentlicher et al, 1974;Fabiato and Fabiato, 1975). Load sensitivity also disappears in a caffeine medium (Lecarpentier et al, 1979;Poggesi et al, 1979) which partially inhibits the sarcoplasmic reticulum (Weber and Herz, 1968). Furthermore, load sensitivity of relaxation is not observed in the frog ventricular strip (Brutsaert et al, 1978b) where the sarcoplasmic reticulum is scarcely developed (Staley and Benson, 1968), nor in newborn rat myocardium (personal observation) in which the sarcoplasmic reticulum is not yet functional (Fabiato and Fabiato, 1978).…”
Section: Time Course Of Sarcomere Relaxation Occurring In Two Phasesmentioning
confidence: 81%
“…A load-independent relaxation, associated with a low rate of activation decay secondary to a slow rate of calcium uptake, has been described in frog ventricle (4), in smooth muscle (25) and in mammalian myocardium after interventions leading to impaired function of the sarcoplasmic reticulum (18,23). However, a slow activation decay in atrial muscle is rather unlikely, since the tension decline during relaxation is fast.…”
Section: Introductionmentioning
confidence: 94%
“…This factor can be identified as a delayed decline of activation. In fact, a prolonged decay of activation is associated with a reduced sensitivity of relaxation to mechanical conditions in several experimental conditions: e.g., after addition of high concentrations of caffeine (25) or Sr 2+ for Ca 2+ substitution (26). A possible explanation is that when activation declines slowly, cross bridges broken by the movement can reform.…”
Section: Time Course and Load Sensitivity Of Relaxationmentioning
confidence: 97%
“…For example, load sensitivity of the relaxation is reduced when activation is prolonged by caffeine or by the replacement of calcium by strontium (25,26). Furthermore, relaxation is less sensitive to loading conditions in atrial than in ventricular myocardium, or in rat than in cat papillary muscle, and this can be attributed to a difference in the speed of cross bridge cycling, as suggested by the values of shortening velocity and ATPase activity (27).…”
Section: Introductionmentioning
confidence: 95%